Feasibility of a Behavioral Intervention to Reduce Psychological Distress in Mechanically Ventilated Patients. Issue 4 (1st October 2020) - Tan, Yanni; Gajic, Ognjen; Schulte, Phillip J.; Clark, Matthew M.; Philbrick, Kemuel L.; Karnatovskaia, Lioudmila V.
ABSTRACT: Many survivors of acute respiratory failure suffer from mood disorders following discharge from the hospital. We investigated the feasibility of intensivists delivering psychological support based on positive suggestion (PSBPS) to 20 intubated patients to reduce their psychological distress. Thirteen patients completed follow-up surveys. Of those, 9 remembered the intensive care unit physician talking to them, and 7 described it as comforting. Five patients (38%) met criteria for anxiety, depression, and acute stress. In comparison to historical controls, intervention may be associated with lower estimated odds of anxiety. PSBPS can be performed with patients in parallel with medical treatment to potentially reduce psychological morbidity and to humanize critical care. A larger randomized study is warranted to assess the efficacy of PSBPS.